Pengaruh Model Picture and Picture Berbantuan Media Story Puzzle terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Aulina Asti Amini; Muhammad Erfan; Aisa Nikmah Rahmatih (Mataram University, 2026)
This research is motivated by the low learning outcomes of students in science and social subjects, so it is necessary to implement a learning model that is able to increase student involvement in the learning process. This research aims to determine the effect of the Picture and Picture model assisted by Story Puzzle media on the science and social learning outcomes of class IV students at SDN 2 Pengadangan. This research uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research subjects consisted of an experimental class that received learning using the Picture and Picture model assisted by Story Puzzle media and a kontrol class that used direct learning. Data collection techniques are carried out through learning outcomes tests that meet the validity and reliability criteria. The research results showed that there was a significant difference between student learning outcomes in the experimental class and the kontrol class, with higher improvements in the experimental class. The results of the hypothesis test show a calculated t value of -3.505 and a significance value (p-value) of 0.001 which is smaller than 0.025. Thus, the Picture and Picture model assisted by Story Puzzle media has a significant effect on the science and social learning outcomes of class IV students at SDN 2 Pengadangan. These findings indicate that the use of the Picture and Picture model assisted by Story Puzzle media can be an effective learning alternative to improve student learning outcomes.